Green Synthesis of Fe3O4 Nanoparticles and Its Application in Preparation of Fe3O4/Cellulose Magnetic Nanocomposite: A Suitable Proposal for Drug Delivery Systems - Azizi, Amir (Journal of inorganic and organometallic polymers and materials, 2020)
In this study, magnetic iron oxide nanoparticles (Fe 3 O 4 ) were produced by a green method, using aqueous extract of spent-tea waste as the reducing agent, which was subsequently used to prepare the magnetic and biodegradable Fe 3 O 4 /cellulose nanocomposite. The nanostructures were compared using advanced techniques such as UV–Vis spectrophotometry, Fourier transform infrared, X-ray spectroscopy, imaging by electron microscopy, thermal analysis, and vibrating-sample magnetometery. The data from the analyses showed that the synthesized nanocomposite had a spherical shape with an average particle size of 15.5 nm, which is smaller than the mean (28 nm) of the pure Fe 3 O 4 nanoparticles. These results also showed that the prepared nanocomposite had a higher thermal resistance (450–800 °C) compared to pure cellulose. Another important feature of the nanoscale was the magnetic property (25 emu/g), which was smaller than that obtained in pure Fe 3 O 4 nanoparticles (45 emu/g). In addition, the swelling capacity was studied as one of the functional capabilities of the nanocomposite, which was 139.3 g/g, more than the swell capacity obtained for pure cellulose (66.8 g/g). According to the results, the prepared Fe 3 O 4 /cellulose nanocomposite is suggested to be applied in metronidazole drug delivery system regarding its suitable and acceptable properties, such as high absorption capacity, controlled magnetic transferability and biodegradability as well as non-toxicity.